The Role of the Young Generation of Bangka Belitung thru Social Communities in The Implementation of Civic Competences Values - Muhamad Hijran; Reza Adriantika Suntara; Hanifa Intan Desiga (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to describe how Bangka Belitung youth implement civic competences through three social communities: Bangka Environment Creative of “Kawa,” Hopeeducation, and Pokdarwis Perlintar, focusing on their environmental, educational, social, and local resource management activities. Methodology: This study employed a qualitative descriptive design. Data were collected through direct observation, semi-structured interviews, and document analysis involving community administrators, active members, young volunteers, activity archives, photographs, social media publications, and program reports. Data were analyzed systematically through data reduction, data display, conclusion drawing, and source and method triangulation. Main Findings: The three communities contributed in different but complementary ways. Environmental efforts, waste education, tree planting and collaborative action reinforced Kawa’s ecological awareness. Educational service developed volunteerism, benevolence, social sensitivity and moral responsibility. Post mining tourist revitalization improved involvement, local economic empowerment, and environmental responsibility of Pokdarwis Perlintar. Together they acquired civic knowledge, civic skills and civic disposition. Novelty/Originality of this study: This study offers a comprehensive examination of three youth led groups operating in the environmental, educational social, and post-mining tourist sectors in Bangka Belitung. It contributes to the scholarship of civic competence by showing that non formal community participation can be a pedagogical experience for civic knowledge, civic skills, and civic disposition simultaneously in a unique Indonesian local, island, and post mining setting.